Kajian Profil Kearifan Lokal Lilifuk: Traditional Ecological Knowledge (Tek) di Desa Kuanheum - Joi Alfreddi Surbakti; Sondang P.P Leonak (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2020)
This research was conducted in Kuanheum Village, West Kupang District, Kupang Regency, East Nusa Tenggara from May to June 2020. The purpose of this study is to describe the values of local wisdom found in the coastal communities of Kuanheum Village, Kupang Regency. The research method used in this research is descriptive qualitative method and case studies with an ethnographic study approach. The number of respondents taken was 30 people. Respondents consist of traditional elders, village heads, and representatives of non-governmental organizations. The management concept of Lilifuk is a community based management model to build management based on a subjective approach and a structural approach.